2018
DOI: 10.1155/2018/3459612
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Improves the Viability and Function of Cryopreserved Human Nucleus Pulposus‐Derived Mesenchymal Stem Cells

Abstract: Nucleus pulposus-derived mesenchymal stem cells (NPMSCs) have shown a good prospect in the regeneration of intervertebral disc (IVD) tissues. However, fresh NPMSCs are not always readily available for basic research and clinical applications. Therefore, there is a need for an effective long-term cryopreservation method for NPMSCs. The aim of this study was to determine whether adding icariin (ICA) to the conventional cryoprotectant containing dimethyl sulfoxide (DMSO) had a better cryoprotective effect for NPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…Because the direct treatment effects of TGF-b signaling have been introduced in detail above, the treatments of TGF-b combined with tissue engineering technology for IVD degeneration will be mainly discussed below. Mesenchymal stem cell (MSC)-based tissue engineering treatment has been widely contemplated for the repair of IVD degeneration and has shown promising perspectives 108,109 . Studies show that TGF-b plays a vital role in it 110,111 .…”
Section: The Treatment Prospect Of Tgf-b Signaling In Ivd Degenerationmentioning
confidence: 99%
“…Because the direct treatment effects of TGF-b signaling have been introduced in detail above, the treatments of TGF-b combined with tissue engineering technology for IVD degeneration will be mainly discussed below. Mesenchymal stem cell (MSC)-based tissue engineering treatment has been widely contemplated for the repair of IVD degeneration and has shown promising perspectives 108,109 . Studies show that TGF-b plays a vital role in it 110,111 .…”
Section: The Treatment Prospect Of Tgf-b Signaling In Ivd Degenerationmentioning
confidence: 99%
“…Many studies confirmed that MSCs derived from the NP, AF, and CEP have the ability to differentiate into osteogenic, adipogenic, and chondrogenic lineages [35][36][37][38][39][40][41][42][43][44] . Liu et al [49] compared the characteristics of three types of MSCs derived from human IVD including NP-MSCs, AF-MSCs, and CEP-MSCs and found that they showed similar multilineage differentiation capacities, whereas CEP-MSCs showed the best migration and invasion potency.…”
Section: Multi-differentiationmentioning
confidence: 99%
“…The most often used dimethyl sulfoxide is regarded as the standard cryoprotectant which may cause cytotoxicity to MSCs [69,70] . A recent study by Chen et al [44] showed that the addition of Icariin known as antioxidant to the conventional freezing medium could improve the viability and function of cryopreserved human NP-MSCs, which may be a new method of preserving stem/progenitor cells in the IVD for ERS (Table 2).…”
Section: Refmentioning
confidence: 99%
“…We and other researchers from different research groups have isolated, cultured, and identified endogenous IVD MSCs from nucleus pulposus (NP) [8], annulus fibrosus (AF) [9], cartilage endplate (CEP) [10], and stem cell niche areas in IVD [11]. These endogenous MSCs can serve as the seed cells for endogenous repair of IVD degeneration.…”
Section: Introductionmentioning
confidence: 99%